Similar material for SAP porous lightweight concrete buffer layer dislocation model test and preparation method thereof

By using similar materials prepared by gypsum, diatomaceous earth, water and saturated polymer water-absorbing resin aggregates, the problem of difficult to prepare SAP porous lightweight concrete materials suitable for scale model tests in the prior art is solved, and the strength and brittle characteristics of the material are reflected, and the accuracy of the test results is improved.

CN119551958APending Publication Date: 2025-03-04CCCC SECOND HIGHWAY CONSULTANTS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411468631.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

In the research on the anti-fault resistance of crossing live fault tunnels, it is difficult for the prior art to effectively prepare SAP porous lightweight concrete similar materials for scale model tests, which affects the accuracy of the test results.

Method used

Similar materials are prepared using gypsum, diatomaceous earth, water and saturated polymer water-absorbing resin aggregates. By controlling the proportion of raw materials and the particle size of saturated SAP aggregates, the peak compressive strength and volume compression ratio of the material meet the requirements.

Benefits of technology

The prepared similar materials can reflect the strength and brittleness characteristics of SAP porous lightweight concrete, and are suitable for fault staggered model tests, improving the accuracy of the test results.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119551958A_ABST
    Figure CN119551958A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of SAP porous lightweight concrete materials, and provides a similar material for SAP porous lightweight concrete buffer layer dislocation model tests, the similar material comprises the following raw materials: paste, diatomite, water and saturated polymer water-absorbent resin aggregate, wherein the saturated high-molecular water-absorbent resin aggregate is prepared by soaking high-molecular water-absorbent resin aggregate in a Na2CO3 solution to reach a saturated state. The raw materials needed for preparing the similar material are low in cost and wide in source, meanwhile, the preparation method is simple, the technical requirements of a reduced scale model test can be met, and wide applicability is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of SAP porous lightweight concrete materials, and in particular relates to a similar material used for a SAP porous lightweight concrete buffer layer dislocation model test and a preparation method thereof. Background Art

[0002] The isolation buffer technology based on the brittle buffer theory has important engineering significance and research value in the study of the anti-dislocation of tunnels crossing active faults. The porous lightweight concrete prepared with polymer water-absorbing resin (SAP) as a pore-forming agent has great potential as a buffer layer material for the anti-dislocation design of tunnels crossing active faults. Therefore, it is necessary to carry out the dislocation model test of the SAP porous lightweight concrete buffer layer. However, due to the limitations of the test equipment conditions, the scaled model test is usually used to carry out related research. Therefore, the mechanical properties of the SAP porous lightweight concrete similar materials filled with the buffer layer become the key to determine the accuracy of the scaled model test results. SAP porous lightweight concrete has certain strength and brittle characteristics. As a buffer layer material, it provides certain strength support when there is no active fault dislocation, and can cause brittle failure when dislocation occurs, providing a large space to absorb displacement and protect the tunnel lining structure. Therefore, its similar materials should have similar mechanical properties.

[0003] The present invention proposes a similar material and a preparation method thereof for SAP porous lightweight concrete buffer layer dislocation model test, and takes the compressive strength peak value and the system compression rate after compression failure as similarity indicators to ensure that its mechanical properties are suitable for fault dislocation model test. Summary of the invention

[0004] The object of the present invention is to provide a similar material for a SAP porous lightweight concrete buffer layer dislocation model test and a preparation method thereof, so as to ensure that its mechanical properties are suitable for a fault dislocation model test.

[0005] To achieve the above object, the present invention adopts the following technical solutions:

[0006] A similar material used for SAP porous lightweight concrete buffer layer dislocation model test, composed of the following raw materials:

[0007] Gypsum, diatomaceous earth, water and saturated high molecular water absorbent resin aggregate, wherein the saturated high molecular water absorbent resin aggregate is obtained by immersing the high molecular water absorbent resin aggregate in a Na2CO3 solution to reach a saturated state.

[0008] Furthermore, in terms of mass ratio, gypsum: diatomaceous earth: water = 0.7: 0.3: 0.9, and the volume ratio of the mixed slurry formed by mixing the saturated SAP aggregate with gypsum, diatomaceous earth and water is 0.4:1.

[0009] Furthermore, the concentration of the Na2CO3 solution is 0.2 mol / L.

[0010] Furthermore, the peak compressive strength of the similar material used for the SAP porous lightweight concrete buffer layer dislocation model test is 0.05-0.09 MPa, and the volume compression rate is 20%-25%.

[0011] Furthermore, the particle size of the saturated high molecular water-absorbing resin aggregate is 10 mesh to 20 mesh.

[0012] The above-mentioned method for preparing similar materials for the SAP porous lightweight concrete buffer layer dislocation model test specifically comprises the following steps:

[0013] S1: Place the polymer water-absorbing resin aggregate in a Na2CO3 solution and soak it until saturated for later use;

[0014] S2: Gypsum, diatomaceous earth and water are prepared in proportion, mixed and stirred into a slurry, and saturated polymer water-absorbent resin aggregate is added, and the mixture is mixed and mixed to obtain a polymer water-absorbent resin mortar;

[0015] S3: The polymer water-absorbing resin mortar described in step S2 is subjected to molding, vibration, solidification, demoulding and curing treatments in sequence to obtain a similar material for the SAP porous lightweight concrete buffer layer dislocation model test.

[0016] Furthermore, in step S1, the concentration of the Na2CO3 solution is 0.2 mol / L.

[0017] Furthermore, in step S2, the mass ratio is gypsum: diatomaceous earth: water = 0.7:0.3:0.9, and the volume ratio of the mixed slurry formed by mixing the saturated SAP aggregate with gypsum, diatomaceous earth and water is 0.4:1.

[0018] Furthermore, in step S3, the curing time condition is 10 days.

[0019] The present invention has the following beneficial effects:

[0020] 1. The present invention uses the peak compressive strength and volume compression rate as similarity indicators to prepare the SAP porous lightweight concrete similar material, which can reflect the strength characteristics of the material while also reflecting the brittle characteristics of the material, and is suitable for the SAP porous lightweight concrete buffer layer structure dislocation model test.

[0021] 2. The raw materials required for preparing similar materials in the present invention are low in cost and widely available, and the preparation method is simple, which can meet the technical requirements of scale model tests and has wide applicability. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The present invention is a flow chart of the method for preparing similar materials of the SAP porous lightweight concrete buffer layer dislocation model.

[0023] Figure 2 It is a stress-strain curve diagram of similar material samples prepared in Example 1 of the present invention and Comparative Examples 1-2.

[0024] Figure 3 It is a comparison chart of the uniaxial compressive strength distribution values ​​of similar material samples prepared in Example 1 of the present invention and Comparative Examples 1-2.

[0025] Figure 4 It is a comparison chart of the volume compression rate distribution values ​​of similar material samples prepared in Example 1 of the present invention and Comparative Examples 1-2. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below through specific embodiments. The specific embodiments described in detail herein are only used to explain the present invention, but are not used to limit the scope of the present invention.

[0027] It should be noted that the experimental methods described in the following embodiments are conventional methods unless otherwise specified, and the reagents and materials can be obtained from commercial channels unless otherwise specified.

[0028] The SAP concrete material involved below is prepared by mixing sulphoaluminate cement: saturated SAP aggregate: ordinary river sand: water in the ratio of 10:10:5:3.

[0029] Embodiment 1:

[0030] A similar material for a SAP porous lightweight concrete buffer layer dislocation model test is selected. The mass ratio of gypsum, diatomaceous earth and water is 0.7:0.3:0.9, and the concentration of Na2CO3 solution is 0.2 mol / L. SAP aggregate is immersed in the Na2CO3 solution to reach a saturated state to obtain saturated SAP aggregate. The saturated SAP aggregate with a saturated particle size of 10 mesh to 20 mesh is selected, and the volume ratio of the mixed slurry formed after mixing with gypsum, diatomaceous earth and water is 0.4:1. Three cylindrical specimens with a size of 50 mm*100 mm are prepared.

[0031] The above raw materials are prepared according to the following steps:

[0032] S1: Place SAP aggregate in 0.2 mol / L Na2CO3 solution and soak until saturated for later use;

[0033] S2: Select gypsum and diatomaceous earth according to the proportion, and mix the dry materials evenly;

[0034] S3: adding a corresponding amount of water to the dry material in step S2 to form a slurry, and stirring thoroughly;

[0035] S4: adding saturated SAP aggregate in volume ratio to the slurry in step S3, and mixing to obtain SAP mortar;

[0036] S5: pouring the SAP mortar in step S4 into the mold, vibrating while pouring the slurry to prevent the slurry from stratifying and expelling bubbles;

[0037] S6: After pouring, demould after initial solidification and naturally cure for 10 days in indoor environment.

[0038] The mechanical parameters of similar materials prepared for the SAP porous lightweight concrete buffer layer dislocation model test are shown in Table 1 and Figure 3-4 shown.

[0039] Table 1

[0040]

[0041]

[0042] According to the test results in the above table, the compressive strength and volume compression rate of the similar material prepared in this embodiment 1 meet the corresponding performance of the ideal material for the fault dislocation model test (the compressive strength of the ideal material is 0.05-0.09 / MPa, and the volume compression rate after compressive failure is 20%-25%). Therefore, the mechanical property parameters of the similar material prepared in this embodiment 1 all meet the requirements of the SAP porous lightweight concrete buffer layer dislocation model test, and thus the similar material prepared by this ratio meets the requirements.

[0043] Comparative Example 1:

[0044] A similar material for the SAP porous lightweight concrete buffer layer dislocation model test is selected, the mass ratio of plaster, diatomaceous earth and water is 0.7:0.3:0.9, the concentration of Na2CO3 solution is 0.2 mol / L, the saturated particle size of SAP aggregate is 10 mesh to 20 mesh, the volume ratio of the mixed slurry formed by mixing the saturated SAP aggregate with gypsum, diatomaceous earth and water is 0.3:1, and three φ50mm*100mm cylindrical specimens are prepared.

[0045] The above raw materials are prepared according to the following steps:

[0046] S1: Place SAP aggregate in 0.2 mol / L Na2CO3 solution and soak until saturated for later use;

[0047] S2: Select a certain amount of gypsum, diatomaceous earth and water according to a certain ratio, and mix the dry materials evenly;

[0048] S3: adding a corresponding amount of water to the dry material in step S2 to form a slurry, and stirring thoroughly;

[0049] S4: adding a corresponding volume fraction of saturated SAP aggregate to the slurry in step S3, and mixing the mixture to obtain SAP mortar;

[0050] S5: pouring the SAP mortar in step S4 into the mold, vibrating while pouring the slurry to prevent the slurry from stratifying and expelling bubbles;

[0051] S6: After pouring, demould after initial solidification and naturally cure for 10 days in indoor environment.

[0052] The mechanical parameters of similar materials prepared for the SAP porous lightweight concrete buffer layer dislocation model test are shown in Table 2 and Figure 3-4 shown.

[0053] Table 2

[0054]

[0055] According to the test results in the above table, the mechanical property parameters of similar materials do not meet the requirements of the SAP porous lightweight concrete buffer layer dislocation model test, so the similar materials prepared by this mix ratio do not meet the requirements, further indicating the importance of the material ratio in the present invention.

[0056] Comparative Example 2:

[0057] A similar material for a SAP porous lightweight concrete buffer layer dislocation model test is selected, wherein the mass ratio of plaster, diatomaceous earth and water is 0.7:0.3:0.9, the concentration of Na2CO3 solution is 0.2 mol / L, the saturated particle size of SAP aggregate is 30-60 mesh, the volume ratio of the mixed slurry formed by mixing the saturated SAP aggregate with gypsum, diatomaceous earth and water is 0.3:1, and three cylindrical specimens of φ50mm*100mm are prepared.

[0058] The above raw materials are prepared according to the following steps:

[0059] S1: Place SAP aggregate in 0.2 mol / L Na2CO3 solution and soak until saturated for later use;

[0060] S2: Select a certain amount of gypsum, diatomaceous earth and water according to a certain ratio, and mix the dry materials evenly;

[0061] S3: adding a corresponding amount of water to the dry material in step S2 to form a slurry, and stirring thoroughly;

[0062] S4: adding a corresponding volume fraction of saturated SAP aggregate to the slurry in step S3, and mixing the mixture to obtain SAP mortar;

[0063] S5: pouring the SAP mortar in step S4 into the mold, vibrating while pouring the slurry to prevent the slurry from stratifying and expelling bubbles;

[0064] S6: After pouring, demould after initial solidification and naturally cure for 10 days in indoor environment.

[0065] The mechanical parameters of similar materials prepared for the SAP porous lightweight concrete buffer layer dislocation model test are shown in Table 3 and Figure 3-4 shown.

[0066] Table 3

[0067]

[0068] According to the test results in the above table, the mechanical property parameters of similar materials do not meet the requirements of the SAP porous lightweight concrete buffer layer dislocation model test, so the similar materials prepared by this mix ratio do not meet the requirements, further indicating the importance of the material ratio in the present invention.

[0069] In addition, uniaxial compression tests were performed on similar materials obtained in Example 1 and Comparative Examples 1-2, and the results were as follows: Figure 2 As shown by Figure 2 It can be seen that the uniaxial compressive strength of the material prepared in Example 1 meets the requirements of ideal similar materials. At the same time, its brittle failure characteristics after reaching the peak strength are most obvious, and it is also most similar to the SAP concrete material.

[0070] The above embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several modifications and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.

Claims

1. A similar material for SAP porous lightweight concrete buffer layer dislocation model test, characterized in that: It is composed of the following raw materials: Gypsum, diatomaceous earth, water and saturated high molecular water absorbent resin aggregate, wherein the saturated high molecular water absorbent resin aggregate is obtained by immersing the high molecular water absorbent resin aggregate in a Na2CO3 solution to reach a saturated state.

2. A similar material for SAP porous lightweight concrete buffer layer dislocation model test according to claim 1, characterized in that: In terms of mass ratio, gypsum: diatomaceous earth: water = 0.7:0.3:0.9, and the volume ratio of the mixed slurry formed by mixing the saturated SAP aggregate with gypsum, diatomaceous earth and water is 0.4:

1.

3. A similar material for SAP porous lightweight concrete buffer layer dislocation model test according to claim 1, characterized in that: The concentration of the Na2CO3 solution is 0.2 mol / L.

4. A similar material for SAP porous lightweight concrete buffer layer dislocation model test according to claim 1, characterized in that: The peak compressive strength of the similar material used for the SAP porous lightweight concrete buffer layer dislocation model test is 0.05-0.09MPa, and the volume compression rate is 20%-25%.

5. A similar material for SAP porous lightweight concrete buffer layer dislocation model test according to claim 1, characterized in that: The particle size of the saturated high molecular water-absorbing resin aggregate is 10-20 meshes.

6. A method for preparing a similar material for a SAP porous lightweight concrete buffer layer dislocation model test as claimed in any one of claims 1 to 5, characterized in that: The specific steps include: S1: Place the polymer water-absorbing resin aggregate in a Na2CO3 solution and soak it until saturated for later use; S2: Gypsum, diatomaceous earth and water are prepared in proportion, mixed and stirred into a slurry, and saturated polymer water-absorbent resin aggregate is added, and the mixture is mixed and mixed to obtain a polymer water-absorbent resin mortar; S3: The polymer water-absorbing resin mortar described in step S2 is subjected to molding, vibration, solidification, demoulding and curing treatments in sequence to obtain a similar material for the SAP porous lightweight concrete buffer layer dislocation model test.

7. The preparation method according to claim 6, characterized in that: In step S1, the concentration of the Na2CO3 solution is 0.2 mol / L.

8. The preparation method according to claim 6, characterized in that: In step S2, the mass ratio is gypsum: diatomaceous earth: water = 0.7:0.3:0.9, and the volume ratio of the mixed slurry formed by mixing the saturated SAP aggregate with gypsum, diatomaceous earth and water is 0.4:

1.

9. The preparation method according to claim 6, characterized in that: In step S3, the curing time condition is 10 days.